2022
DOI: 10.1007/s10734-022-00924-7
|View full text |Cite
|
Sign up to set email alerts
|

Celebrating Higher Education’s 50 years: trends, absences, and opportunities

Abstract: The journal, Higher Education (HE), was established in 1972 and is currently one of the leading international journals in higher education studies. By using bibliometric techniques, a systematic review, and a social network analysis, this review article provides an overview of the main patterns of publications in HE during its history. The findings show that (i) the volume of articles has been continuously increasing, with a particular marked uplift since 2007; (ii… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 50 publications
(114 reference statements)
1
1
0
Order By: Relevance
“…Our findings in this study, along with this clear trend in the literature, indicate that higher education research is increasingly diverse in terms of topics covered. This argument also echoes the discussions provided in recent studies (Cantwell et al, 2022;Guzmán-Valenzuela et al, 2022) that higher education research has developed significantly in the last decades and that increasingly more studies by more diverse researchers from different parts of the world are publishing in higher education journals.…”
Section: Discussion: Seven Patternssupporting
confidence: 70%
See 1 more Smart Citation
“…Our findings in this study, along with this clear trend in the literature, indicate that higher education research is increasingly diverse in terms of topics covered. This argument also echoes the discussions provided in recent studies (Cantwell et al, 2022;Guzmán-Valenzuela et al, 2022) that higher education research has developed significantly in the last decades and that increasingly more studies by more diverse researchers from different parts of the world are publishing in higher education journals.…”
Section: Discussion: Seven Patternssupporting
confidence: 70%
“…Hence, higher education studies developed as a significant area of research in the US first, and the body of literature in the US is larger and older than others (Tight, 2007). However, the importance of higher education is growing globally (Guzmán-Valenzuela et al, 2022;Marginson, 2016). Thus, the general expectation would be that the area of higher education research will follow suit and have a more globally inclusive perspective.…”
Section: Previous Mapping Of the Fieldmentioning
confidence: 99%
“…Prior research suggests that higher education research "has been especially nationally oriented and strongly rooted in higher education systems" (Guzmán-Valenzuela et al, 2022, p. 1188, a feature that was also noted by Tight (2014) in the broad field of education studies. However, our data shows that among the articles published by Chinese scholars in the three journals, international collaborative articles dominated the publication pattern.…”
Section: Growth Trend and Authorshipmentioning
confidence: 89%
“…Based on an analysis of publications from 33 core higher education journals indexed in Scopus from 1996 to 2018, Akbaritabar and Barbato (2021) discovered that 90% of the publications were authored by institutions within a single country, while only 10% were authored by institutions from two or more countries. In their analysis of the published articles in Higher Education from 1972 to 2022, Guzmán-Valenzuela et al (2022) showed that 44.5% of articles had a single author, 44.6% were authored within a single country, and only 10.9% were international collaborative articles. Finally, the field of higher education exhibits significant imbalances.…”
Section: The Field Of Higher Education Researchmentioning
confidence: 99%
See 1 more Smart Citation